PEMBUATAN ALAT PERAGA MOTOR BAKAR 4-LANGKAH UNTUK MENDUKUNG PEMBELAJARAN SISTEM KBK - Darsin, Mahros (Jurnal Pengembangan Pendidikan, 2006)
Abstract. In implementing competence based curriculum it needssupport of resources, one of them is laboratory equipment. Mechanicalengineering students should understand how the engine run, what its componentsand how is ignition work. Theoretical study could not make them fullyunderstood, whereas to mount and dismount an engine block is time consuming andcostly.  The moderate way to understandthem is by observing a model of gasoline engine. The project aim is to designand to manufacture a used 4-stroke block engine motorcycle being a model.Design considerate that the model should able to show how is an engine works,how the work of ignition, and what are components of transmission.Manufacturing consideration is that the engine block should not machine thebearing and supporting posts. Manufacturing of engine block was carried out atmachining laboratory by an-5mm end mill. Assembling the component to themachined block shows that the model can fulfill the requirements. Keywords:  model, 4-strokes gasoline engine